Why Do Markets Move Together? An Investigation of u.s.-japan Stock Return Comovements. - Karolyi, G Andrew; Stulz, Rene M (Journal of Finance, 1996)
This article explores the fundamental factors that affect cross-country stock return correlations. Using transactions data from 1988 to 1992, the authors construct overnight and intraday returns for a portfolio of Japanese stocks using their NYSE-traded American depository receipts and a matched-sample portfolio of U.S. stocks. They find that U.S. macroeconomic announcements, shocks to the yen/dollar foreign exchange rate and Treasury bill returns, and industry effects have no measurable influence on U.S. and Japanese return correlations. However, large shocks to broad-based market indices (Nikkei Stock Average and Standard and Poor's 500 Stock Index) positively impact both the magnitude and persistence of the return correlations.